2021
DOI: 10.1177/15266028211028207
|View full text |Cite
|
Sign up to set email alerts
|

“Awake” Spinal Cord Monitoring Under Local Anesthesia and Conscious Sedation in Fenestrated and Branched Endovascular Aortic Repair

Abstract: Introduction Endovascular repair of thoracoabdominal aortic aneurysms carries a risk of spinal cord ischemia, the causes of which remain uncertain. We hypothesized that local anesthesia (LA) with conscious sedation could abrogate the potential suppressive cardiovascular effects of general anesthesia (GA) and facilitate intraoperative monitoring of neurological function. Here, we examine the feasibility of this technique during fenestrated (FEVAR) or branched endovascular aortic repair (BEVAR). Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, the absence of an alternative to general anesthesia remains, thereby preventing treatment for certain high-risk patients. Abisi et al 3 have reported the feasibility of complex endovascular aortic cases using local anesthesia and conscious sedation in a cohort of 44 patients. Severe pulmonary disease can be a contraindication to general anesthesia when weaning from mechanical ventilation would likely be difficult during the postoperative period, but also to conscious sedation as was the case with our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the absence of an alternative to general anesthesia remains, thereby preventing treatment for certain high-risk patients. Abisi et al 3 have reported the feasibility of complex endovascular aortic cases using local anesthesia and conscious sedation in a cohort of 44 patients. Severe pulmonary disease can be a contraindication to general anesthesia when weaning from mechanical ventilation would likely be difficult during the postoperative period, but also to conscious sedation as was the case with our patient.…”
Section: Discussionmentioning
confidence: 99%
“…It also improves spinal cord monitoring as any neurological deficit can be depicted instantly at the end of the procedure. 3 However, it is important to note the risks of conversion to general anesthesia in those high-risk patients who are offered this alternative. This case demonstrated it to be a safe alternative; however, a lack of data to support this strategy remains.…”
Section: Discussionmentioning
confidence: 99%